2018
DOI: 10.1111/bjc.12186
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative absorption, mind‐wandering, and attention‐deficit symptoms: Associations with obsessive‐compulsive symptoms

Abstract: Dissociative absorption is a personality tendency that may interact with obsessive-compulsive symptoms, and thus, it may deserve clinical attention when treating obsessive-compulsive disorder (OCD) Dissociative absorption might bring about an unnecessary diagnosis of attention-deficit hyperactivity disorder (ADHD) in individuals with obsessive-compulsive symptoms, and thus, it should be screened for. This study was based on a non-clinical sample; future studies should replicate the findings among samples with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 70 publications
0
30
0
Order By: Relevance
“…Similarly, Smallwood and Schooler (2015) have noted that whereas poor mood has been related to mind-wandering in general, it is especially related to mind-wandering about the past. Importantly, despite the similarity between mind-wandering and dissociative ABS, Soffer-Dudek (2018) has found that these constructs are empirically disparate. Theoretically, dissociative ABS is defined by the intensity of focus on the stimuli (to the point of obliviousness to other stimuli), whereas mind-wandering is defined by the nature of the stimuli (internal rather than external; Soffer-Dudek, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Smallwood and Schooler (2015) have noted that whereas poor mood has been related to mind-wandering in general, it is especially related to mind-wandering about the past. Importantly, despite the similarity between mind-wandering and dissociative ABS, Soffer-Dudek (2018) has found that these constructs are empirically disparate. Theoretically, dissociative ABS is defined by the intensity of focus on the stimuli (to the point of obliviousness to other stimuli), whereas mind-wandering is defined by the nature of the stimuli (internal rather than external; Soffer-Dudek, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to depersonalization‐derealization, dissociative absorption is also elevated in PTSD (Armour et al, 2014; Özdemir et al, 2015) but unrelated to childhood trauma (Irwin, 1999; Somer & Herscu, 2017). In recent years it has been specifically associated with OCD (Soffer‐Dudek, 2017a, 2019; Soffer‐Dudek et al, 2015) and sleepiness (Soffer‐Dudek et al, 2017). Thus, additional frameworks for understanding the aetiology of dissociation are needed, when considering a broad range of mild to moderate dissociative experiences and variable (not necessarily highly traumatized) clinical populations.…”
Section: The Path To Dissociative Experiences: a Direct Comparison Of Different Etiological Modelsmentioning
confidence: 99%
“…In relation to ADHD, deficient deactivation of DMN activity during cognitive tasks has consistently been found to be associated with the disorder (e.g., Christakou et al , ; Liddle et al , ). On a conceptual and empirical level, MW is related to constructs such as inattention, daydreaming, and self‐absorption (Soffer‐Dudek, ). Taking these findings together, a recently proposed model suggests that altered activation of the DMN in ADHD might lead to excessive MW that in turn may lead to the inattentive symptoms of ADHD (Bozhilova, Michelini, Kuntsi, & Asherson, ).…”
mentioning
confidence: 99%